Structure-activity relationship around PI-2620 highlights the importance of the nitrogen atom position in the tricyclic core. (15th December 2021) - Kroth, Heiko; Oden, Felix; Serra, Andreia Monica; Molette, Jerome; Mueller, Andre; Berndt, Mathias; Capotosti, Francesca; Gabellieri, Emanuele; Schmitt-Willich, Heribert; Hickman, David; Pfeifer, Andrea; Dinkelborg, Ludger; et al.
Graphical abstract: Highlights: Strong impact of the N -atom position in the tricyclic core on Tau-binding. Field-based alignment of compounds with their experimentally determined IC50 data. Deviation from PI-2620 electrostatic fields lead to a loss of Tau-binding. PI-2620 best compound in terms of potent Tau-binding and high MAO-A selectivity. Abstract: Tau aggregates represent a critical pathology in Alzheimer's disease (AD) and other forms of dementia. The extent of Tau neurofibrillary tangles across defined brain regions corresponds well to the observed level of cognitive decline in AD. Compound 1 (PI-2620 ) was recently identified as a promising Tau positron emission tomography tracer for AD and non-AD tauopathies. To evaluate the impact of the N -atom position with respect to Tau- and off-target binding, tricyclic core analogs of PI-2620 with nitrogen atoms at different positions were prepared. Affinity to aggregated Tau was evaluated using human AD brain homogenates, and their off-target binding was evaluated in a monoamine oxidase A (MAO-A) competition assay. The novel tricyclic core derivatives all displayed inferior Tau binding or MAO-A off-target selectivity, indicating PI-2620 to be the optimal design for high affinity binding to Tau and high MAO-A selectivity.